Social Entrepreneurship in Secondary Education of Assam : Creation and Pursuance of Worthy Opportunities - Deb, Rajdeep; Panda, Nagari Mohan (AMC Indian Journal of Entrepreneurship, 2021)
Social entrepreneurship encompasses activities that usually commence with the very idea of worthy and promising opportunities of serious pursuit. Therefore, academics and practitioners alike have converged their efforts in pursuance of growing social entrepreneurial undertakings within the community. Moreover, it is a well proven fact that for social entrepreneurship to happen, opportunity identification must first occur. While striving to make a progress towards social entrepreneurship, the present paper attempted to examine how social entrepreneurs operating in secondary education of Assam discovered and exploited attractive opportunities. Additionally, the aim of this paper was also to devise a plausible resource strategy to tap opportunities. The method adopted was exploratory in nature and qualitative approach was used. Careful and extensive examination of past literature and entrepreneurship process in the current context produced a proposition.